Multi-stakeholder Partnerships in Global Affairs: Learnings from the International Partnership on Religion and Sustainable Development in Times of Polycrisis Policy and Practice Note - Singh, Khushwant (Religion & development, 2024)
This article argues that coordinated and multilayered cross-sectoral collaborated is required to contribute to sustainable development and respond to the global polycrisis characterized by human-made destruction of the environment, climate change and globalization. Pandemics, regional wars, and banking crises not only create local suffering but increasingly have international consequences, threatening the progress made, be it regarding poverty, education, health, or human rights. The article outlines the potential of multi-stakeholder partnerships as inclusive mechanisms of collaboration in global affairs by exemplarily outlining learnings from the International Partnership on Religion and Sustainable Development (PaRD). Despite the promising potential and contributions of PaRD, the article illustrates the need to overcome the principal problem of imbalanced power allocation in global affairs, as decisions at a global level are usually made by governments, with stakeholders from civil society being involved in pre-consultations but remaining without decision-making power.